Asthma Among Manitoba Workers: Results from the Manitoba Occupational Disease Surveillance System - Elizabeth Rydz; Randy Walld; Mieke W. Koehoorn; Christopher B. McLeod; Paul A. Demers; Cheryl E. Peters; Allen Kraut (Elsevier, 2024)
Background: This study characterized the risk of new-onset asthma among workers in Manitoba, Canada. Methods: Accepted time loss claims from the Workers' Compensation Board of Manitoba from 2006 to 2019, containing workers' occupations and industries, were linked with administrative health data from 1996 to 2020. After restricting the cohort to the first claim per person in an occupation and applying age and coverage exclusions, the cohort comprised 142,588 person-occupation combinations. Asthma cases were identified if workers had at least two medical records for asthma (International Classification of Diseases, Ninth Revision, 493) within a 12-month period, within the 2 years before 3 years after cohort entry. New-onset asthma was identified using a 3-year washout period. Asthma hazard ratios by occupation and industry were estimated using Cox proportional hazard models, adjusted for age, and stratified by sex. Results: Increased asthma risk was observed among workers with known asthmagen exposure, including male veterinary and animal health technologists and technicians (hazard ratio 3.97, 95% CI 1.78-8.86), male fish processing workers (3.40, 1.53-7.57), and male machining tool operators (2.91, 1.72-4.92). Increases were also observed for occupations with unknown or suspected allergens, including gas station attendants, drivers, mail/postal and related workers, public works and maintenance laborers, mine laborers and crane operators, and some indoor worker groups. Decreased risks were observed among nurses and residential and commercial installer and servicers. Conclusion: This database linkage study successfully identified occupations and industries with known sensitizing agents or irritants, and several occupation and industries not typically associated with work-related asthma, warranting further investigation.